Attribution’s Impact on Consumer Response to CSR Efforts with Trust as Moderation - Wijaya, Michelle; SeTin, SeTin; Agustina, Lidya (Jurnal Akuntansi, 2025)
Purpose – This study aims to examine the influence of other-serving attributions, self-serving attributions on consumer responses to CSR efforts when moderated by consumer trust. Design/methodology/approach – This research was conducted in 2024, and the population of this study were students of the Faculty of Digital Business and Law, universities in Bandung and the sampling technique was simple random sampling. This study uses primary data collected through questionnaires in the form of Google Forms. A total of 150 data were collected and analyzed using moderated regression analysis (MRA). Findings – The results show that other-serving attributions positively influence consumer response to CSR efforts while self-serving attributions negatively influence consumer response to CSR efforts. The findings also show that when consumer trust is a moderator, other-serving attributions further increase consumer response to CSR efforts, and conversely, self-serving attributions will further decrease consumer response to CSR efforts. Research limitations/implications – The implication of this study is that companies need to focus on other-serving attributions in CSR communications to increase positive consumer responses, especially when consumer trust is high. This study contributes insights into the importance of building consumer trust in a company's CSR strategy. Keywords: Consumer Response to CSR Efforts, Other-Serving Attributions, SelfServing Attributions, Consumer Trust In Firm.